Self-reported oral health. A cross sectional study in the municipalities with mixed Sami and Norwegian population in Northern and Mid-Norway. - Teterina, Anna (UiT Norges arktiske universitet, 2018)
Background: Detailed data on oral health in the adult population in Northern Norway has been lacking. A number of national studies have reported a north-south gradient in oral health in Norway. Various governmental reports stated that oral health was poorer in Northern Norway, specifically in the municipalities where the proportion of the Sami-population is large. However, no scientific proof of that currently exists. Moreover, no study of self-reported oral health and its determinants has been performed in Northern and Mid-Norway. Aim: This study sought to investigate different aspects of self-reported oral health in the municipalities in Northern- and Mid-Norway with mixed indigenous and non-indigenous populations and assess behavioural determinants of self-reported oral health. Materials and methods: The questionnaire data from the SAMINOR 2 (2012) was used. The study population consisted of 11,325 subjects aged 18-69 years-old living in 25 municipalities in Northern and Mid-Norway. Response rate in the SAMINOR study was 27%. The study sample was described according to demographic and behavioural characteristics, area of residence and prevalence of good SROH. Logistic regression analysis was performed to assess the determinants of poor SROH. Results: Seventy-three-point five percent of study participants reported good oral health. Daily smokers had a 2.63 times higher odds of reporting poor oral health (p<0.001). The participants that brushed their teeth seldom at the age of 10 were 2.59 times more likely to report poor oral health (p<0.001). The participants residing in the Sami-majority area had a 36.4% higher risk of reporting poor oral health (p=0.002). Conclusion: The prevalence of good SROH in the study sample was few percent less than the country average. Daily smoking and seldom tooth brushing at the age of 10 were the strongest predictors of poor SROH. Area of residence was a significant predictor of SROH due to possible structural and geographical differences, and other unique characteristics.